Evaluation of Antitumor and Antioxidant Potential of a Polyherbal Extract on Ehrlich’s Ascites Carcinoma Xenografted Mice - Mukesh Kumar Das; K.Mukkanti; G. Srinivasa Rao; Prafulla Kumar Sahu; L. Silpavathi (Journal of Pharmacy and Nutrition Sciences, 2014)
Objective: Indigenous herbs alone or in combination are widely used in Indian system of medicine to treat innumerable ailments since time immemorial. Many strategies has been adopted to enhance anticarcinogenic responses and to establish therapeutic benefits. Poly herbal extracts (PHE), one of the emerging trends of modern medicine, where the assorted active principles work vibrantly to produce a maximum therapeutic activity with minimal toxicity by virtue of its additive, potentative, synergistic, agonistic or antagonistic effects. Though, Withania somnifera, Oroxylum indicum and Calotropis gigentia are independently established as potent antineoplastic agents, their antitumor and antioxidant perspective in combination is yet to be studied. The proposed study ascertains the assorted antineoplastic and antioxidant potential of the said potent herbs in PHE. Method: The antitumor potency of the PHE at a dose of 400 mg/kg body weight was screened on Ehrlich’s ascites carcinoma (EAC) xenografted swiss albino mice. The in-vivo anti-oxidant activity was investigated on the basis of hepatic anti-oxidant enzymes’ levels. Result: The PHE at the aforementioned dose showed a restoring effect on altered hematological parameters (***P< 0.05 considered to be significant), down turn in ascitic tumor volume and increase in mean survival time. A significant improvement in biochemical parameters (Enzymic antioxidants) was too observed. Conclusion:The study epitomizes the PHE (400 mg/kg body weight) as a potent anti tumor and anti-oxidant preparation with synergistic effects on EAC bearing mice.